PEMANFAATAN INTERAKSI SOSIAL SEBAGAI PROMOSI DIKEDAI SENANG-SENANG - Cecep Abdul wahid; Novi Agustin; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (PT Naureen Digital Education, 2023)
This research is motivated by the role of warung senang-senang as a means of social interaction for young people and the people of Cikampek who come not only to enjoy the food menu but are willing to linger there just for social interaction. Currently, there are a lot of activities that occur in happy stalls such as confiding, organisational meetings, doing assignments, discussions, business meetings and several other activities that make happy stalls a public space for social interaction. This research uses a qualitative method with data collection done by observation, interview The purpose of this visit is to find out the process of social interaction as a promotion in happy-happy shop.